Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1177/070674370404900110
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Psychological Morbidity in West Bank Palestinian Children

Abstract: The prevalence of psychological morbidity among Palestinian children in the West Bank was significantly higher (factor of 2; chi2 = 23.26, df 1, P < 0.001), relative to the level of psychological morbidity determined independently for children in Gaza during 2000. We predict that these rates will have increased substantially owing to the escalated violence that began in this region 2 months after we conducted our study. We further predict that children in Israeli settlements in the West Bank will also exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…We postulate that this is because students in areas with a high risk of exposure to the conflict may be suffering from the after-shocks of the Second Intifada, and may have experienced first-hand the effects of the ongoing conflict in their communities-whether through uprisings in refugee camps, or negative encounters with settlers, or at the separation wall. Based on previous research, we believe that these encounters would have a detrimental psychological effect on students (see Zakrison et al 2004) and could impair their development of various types of executive functions. This is where innovative assessment and learning resources could make the most significant impact on young people's development-by meeting the distinct learning needs of young people in the most difficult learning environments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We postulate that this is because students in areas with a high risk of exposure to the conflict may be suffering from the after-shocks of the Second Intifada, and may have experienced first-hand the effects of the ongoing conflict in their communities-whether through uprisings in refugee camps, or negative encounters with settlers, or at the separation wall. Based on previous research, we believe that these encounters would have a detrimental psychological effect on students (see Zakrison et al 2004) and could impair their development of various types of executive functions. This is where innovative assessment and learning resources could make the most significant impact on young people's development-by meeting the distinct learning needs of young people in the most difficult learning environments.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, close to 60% of youth exposed to violence in the West Bank and Gaza have difficulty functioning in school as a result of the psychological trauma of conflicts (Abdeen et al 2008). Additionally, a significant proportion of Palestinian youth suffer from PTSD, which is thought to detract from their ability to concentrate and perform well in school as a result (Zakrison et al 2004). Prior research has also found that youth in Palestine also suffer from executive function deficits due to conflict (Kanagaratnam and Asbjornsen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Experts in the field have illustrated how most Palestinian children suffer from emotional, behavioural and psychosomatic trauma-related disorders (Espie et al, 2009). For example, in a study carried out in the West Bank, Zakrinson, Shanen, Mortaja, and Hamel (2004) underline how the incidence of psychopathological disorders is particularly evident amongst children. They reported that in the year 2000, 42% of Palestinian children suffered from psychopathological problems.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that in the year 2000, 42% of Palestinian children suffered from psychopathological problems. The most common diagnoses vary from the afore-mentioned emotive-behavioural disorders, to trauma-related disorders, such as moderate and severe post-stress syndromes (Arafat & Boothby, 2004;Miller, El-Masri, Allodi, & Quota, 1999;Zakrinson et al, 2004). In 1993 during the First Intifada, 232 children were killed in clashes with the Israeli armed forces (Middle East Children Alliance [MECA], 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade many studies have documented the emotional burden on Palestinians and their children (Miller, El‐Masri, Allodi, & Qouta, 1999; Thabet, Abed, & Vostanis, 2004; Zakrison, Shahen, Mortaja, & Hamel, 2003) as a result of the ongoing conflict in the Occupied Territories. Along with other studies of children caught up in war and conflict (Loughry & Eyber, 2003), this has established the special needs of Palestinian children (Ressler, Tortorici, & Marcelino, 1993) and their increased risk of developing anxiety, depression and other emotional and behavioural problems, including symptoms of post‐traumatic stress disorder (Qouta, Punamaki, & El‐Sarraj, 2003; Macksoud, Aber, & Cohn, 1996).…”
mentioning
confidence: 99%